Urbanistic strategies of historical cities: workshop revitalization of market square in Lutsk - Криворучко, Ольга; Kryvoruchko, Olha (Lviv Politechnic Publishing House, 2018)
У статті розглянуто умови та доцільність проведення архітектурних воркшопів у рамках передпроектних досліджень території, а саме громадських просторів. Прикладом може служити семінар “Ревіталізація Ринкової площі у Луцьку”, який пройшов у Луцьку, 21–28 березня 2017 р. Організований у рамках проекту COMUS “Міські стратегії історичних міст”, ініційоване спільнотою туристичної інформації та Центру послуг м. Луцька разом із кафедрою містобудування Національного університету “Львівська політехніка”.

The article deals with the conditions and expediency of architectural workshops in the framework of pre-project studies of the territory design, namely public spaces. It is presented on the base of the workshop Revitalization of the Market Square in Lutsk, held in Lutsk, March 21–28, 2017, which was organized within the framework of the COMUS project Urban Strategies of Historic Cities Initiated by the Community of the Tourist Information and Services Center of Lutsk, together with Department of Urban Planing, Lviv Polytechnic National University.
Урбаністичні стратегії історичних міст: семінар “Реалізація ринкової площі в Луцьку”
Keywords: міська стратегія; воркшоп; ревіталізація; громадський простір; простір для відпочинку; історичне місто; ринкова площа; Луцьк; urban strategy; workshop; participative design; revitalization; public space; recreational space; historical city; market square; Lutsk